Mechanisms of COPD exacerbations and relation to exacerbation therapy - Wedzicha, Wisia (Henry Stewart Talks, 2012)
Definition of exacerbations, Breakdown of virus directed exacerbations, Pollution and COPD, Importance of exacerbations, Eclipse study, Poet study, Torch study, Inspire study, Antibiotic use in COPD patients, Non-pharmacological interventions